Feiras de ciências: uma estratégia pedagógica para promoção da alfabetização científico-tecnológica no ensino médio - Fernanda Aires Guedes Ferreira (2021)
The purpose of this research is to understand the development of scientific education in science fairs within school spaces and to examine how and to what extent the subjects’ (students and teachers) various experiences contributed to their education as scientifically literate individuals. This is a case study at Mateus Leme, in Minas Gerais, a city presenting large participation in science fairs at the state and national level, and a consolidated school culture regarding this kind of event. The adopted methods were observation, questionnaires, and interviews. From four public schools of Mateus Leme, 19 teachers and 348 high school students participated in the research. The discussions presented in this research aimed to answer the following questions: 1) What actions and practices emerge from the participation of students and teachers in high-school science fairs? 2) Which elements that promote Scientific and Technological Literacy (STL) are developed in science fairs? 3) How to identify pieces of evidence that science fairs contribute to STL in the school environment? For the data analysis, we developed a tool to analyze the data in two aspects: the first, regarding the TEACHER’s doings and the SCHOOL’s organization in the dynamic of science fairs; the second, regarding the STUDENT’s works themselves. Examining the work of the teachers and its relation with the literature, we picked five indicators that potentialize the science fairs as promoters of STL: 1) multidisciplinarity, the fomenting of partnerships, and networking; 2) perennity and scientific culture; 3) potentialization of scientific initiation; 4) socialization and proximity to the educational community; 5) scientific and technological diffusion. Regarding the teams of students, we verified actions, practices, and active, collaborative, and engaged learning that indicate the process of learning science, of learning about science, and of learning how to do science. The referred practices were analyzed from five indicators of STL occurring in the context of science fairs: 1) approach and appropriation of science; 2) problematization and contextualization; 3) investigative planning; 4) student centrality and autonomy; 5) science interest and appreciation. In the analysis of each STL indicator, we verified that the actions are conducted by the involved subjects according to their experiences with scientific research. We verified that the science fairs at the city of Mateus Leme function as a means of supplying and professionalizing teachers allowing the constitution of authentic projects of scientific initiation. The research has theoretical implications, in proposing a tool for analyzing science fairs in the STL perspective, and practical implications, highlighting the elements that potentialize the STL of teachers and students. Furthermore, this study case aims to inspire educators and schools for similar actions.